Dynamika i zmiany strukturalne we współczesnym międzynarodowym handlu towarowym - Świerkocki, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Since 1950 international merchandise trade has risen faster than world production although the excess of the export growth over output growth was different throughout the period. The rates of global integration varied among the regions and product groups. World trade turnover concentrated in rich regions and rich countries reflecting development asymmetries in the world economy. The differences between rates of trade integration of agriculture, mining and manufacturing became more visible since early seventies. The faster growth of trade in manufactures partly reflects rising flows of parts and components. This type of trade gives less developed countries a better chance to enter world markets. Contemporary trade also encompasses more varieties of goods. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 339-348